Peran Lokasi dan Harga Terhadap Keputusan Mahasiswa Memilih STIE Mahaputra Riau dengan Minat Sebagai Variabel Intervening - Nusyirwan, Nusyirwan; Safrizal, Safrizal; Hidayat, Rahmadani (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
Student interest and decision making to choose a place to continue their education is very important to be understood by every university, so it is necessary to make efforts to always learn about the needs and desires of prospective students. This study aims to determine the role of location and price on student decisions in choosing STIE Mahaputra Riau with interest as an intervening variable. The variables used in this study were location and price as independent variables, decision as the dependent variable, and interest as intervening variables.The data source in this study is primary data, where the data collection method uses a questionnaire method distributed in STIE Mahaputra Riau. The number of respondents in this study was 220 people who were determined by proportional random sampling. The data analysis technique used is path analysis. The results showed that location and price partially had a positive and significant effect on decisions, location and price partially had a positive and significant effect on interest, location and price had a positive and significant effect on decisions through interest as an intervening variable, interest had a positive and significant effect on decisions